The Effect of Entrepreneurship Training on The Sustainability of Msmes Through Digital Literacy and Entrepreneurial Behavior - Deni Nugraha; Eeng Ahman; Disman; Hari Mulyadi (JST (Jurnal Sains dan Teknologi), 2025)
The main problem this research addresses is the low vitality of MSMEs following the socio-economic transformation brought about by the construction of reservoirs, which altered livelihood patterns and market structures. This situation is exacerbated by the suboptimal training in entrepreneurship, digital literacy, and entrepreneurial behavior, which impacts business sustainability. This study aims to analyze and examine the effects of entrepreneurship training, digital literacy, and entrepreneurial behavior on business resilience. A quantitative approach with a survey design was employed. The research subjects consisted of MSME actors in areas affected by reservoir development, selected using proportionate stratified sampling to ensure representation across business strata. Data were collected through a structured questionnaire as the primary research instrument. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to examine the relationships among variables within the proposed model. The findings indicate that the levels of entrepreneurship training, digital literacy, and entrepreneurial behavior among local MSMEs are generally moderate, with entrepreneurship training demonstrating the most significant direct effect on business resilience. The practical implications highlight the necessity of integrated and sustainable training program designs by government agencies and supporting institutions to enhance MSME capacity. In conclusion, MSME resilience is positively influenced by the synergistic integration of entrepreneurship training, digital literacy, and entrepreneurial behavior.